CELLULAR EFFECTS OF EXPOSURE TO PLASTIC MICROPARTICLES IN AQUATIC ORGANISMS - Núñez Nogueira, Gabriel; Cruz Ascencio, Mórvila; Pérez López, Alejandra; Álvarez González, Carlos Alfonso (Kuxulkab’, 2022)
Microplastics and nanoplastics are among the most widely distributed pollutants globally and currently concern humanity, mainly because of their durability and the adverse effects it shows in different organisms, both in terrestrial and aquatic environments. It has been shown in laboratory studies that plastics of various types, either simply or in combination with other toxic compounds or elements, elicit potentially harmful responses at the cellular level, such as cell membrane lysis, modulation of membrane receptors, changes in membrane potentials, alterations in permeability, mitochondrial damage, changes in metabolic activities, generation of reactive oxygen species, genotoxicity, DNA damage and apoptosis. However, our knowledge about the effects of microplastics concentrations in the natural environment needs to be improved.